Severe epistaxis in patients on extracorporeal membranous oxygenator support occurrence and management - Makdisi, George; Wang, I-wen (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
We would like to thank Dr. Mazzeffi and colleagues (1) for the comments on our recently published article entitled “Extra corporeal membrane oxygenation (ECMO) review of a lifesaving technology” (2), as well as reporting their own data regarding severe epistaxis during ECMO support. We agree that bleeding is a frequently encountered complication during ECMO support with reported rates ranging from 10-30%. Bleeding may also occur at surgical sites, cannula sites, or sites of previous invasive procedures. Intrathoracic, abdominal, or retroperitoneal hemorrhage may also occur (2). Case reports of epistaxis associated with ECMO support have been seen in the literature (3,4). Harrison et al. (5) reported 11 patients (30% of all their ECMO series) with aerodigestive bleeding. Among these, seven patients experienced nose or nasopharyngeal bleeding and a total of eight patients needed nasal packing.